Definition, types and general characteristics of forms of public service activities in the field of urban planning - Omelyan, Olena (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article analyzes the structural changes that have occurred during the reform of entities in the field of urban planning in terms of providing administrative services and the implementation of architectural and construction supervision and control. Emphasis is placed on the formation of a renewed service authorized to implement public service activities in the field of urban planning. The criteria for classification of forms of public service activities in the field of urban planning have been determined. The author’s concept of forms of public service activity in the field of urban planning is given. Based on the analysis of forms of public service activities in the field of urban planning, and taking into account the theoretical and methodological foundations, we offer the author’s vision of this concept. The form of public service activity should be understood as ways of expressing specific actions by authorized bodies, for the implementation of the tasks set before them for the implementation of permit-registration and other service activities in the field of urban planning.